Walter Benjamins Ars poetica - Michel Métayer (Recherches Germaniques)
Even though Walter Benjamin wrote and translated poems, his poetic endeavors are seldom mentioned. However, it is possible to decipher a precise conception of poetry in the poetic fragments of his youth, that were written approximately between 1914 and 1922-1925. This will be accomplished in a close reading of his sonnet Wie karg die Maße, that is regarded as an Ars poetica, and of several translations of the Baudelaire-poems Der Schwann and Landschaft. This paper aims, firstly, to show how questions that were later essential for Benjamin are already present, and, secondly, to determine how he deals with them: questions of language and content, image, allegory. The material of literature is the world in which the poet lives, revealing its contradictions.